Intracellular Reduction-Responsive Molecular Targeted Nanomedicine for Hepatocellular Carcinoma Therapy - Ding, Lei; Zhang, Ping; Huang, Xu; Yang, Kunmeng; Liu, Xingkai; Yu, Zhenxiang (Frontiers in Pharmacology, 2022)
The stimuli-responsive polymer-based platform for controlled drug delivery has gained increasing attention in treating hepatocellular carcinoma (HCC) owing to the fascinating biocompatibility and biodegradability, improved antitumor efficacy, and negligible side effects recently. Herein, a disulfide bond-contained polypeptide nanogel, methoxy poly(ethylene glycol)−poly(L-phenylalanine-co-L-cystine) (mPEG−P(LP-co-LC)) nanogel, which could be responsive to the intracellular reduction microenvironments, was developed to deliver lenvatinib (LEN), an inhibitor of multiple receptor tyrosine kinases, for HCC therapy. The lenvatinib-loaded nanogel (NG/LEN) displayed concise drug delivery under the stimulus of glutathione in the cancer cells. Furthermore, the intracellular reduction-responsive nanomedicine NG/LEN showed excellent antitumor effect and almost no side effects toward both subcutaneous and orthotopic HCC tumor-allografted mice in comparison to free drug. The excellent tumor-inhibition efficacy with negligible side effects demonstrated the potential of NG/LEN for clinical molecular targeted therapy of gastrointestinal carcinoma in the future.